Transforming genes of human hematopoietic tumors: frequent detection of ras-related oncogenes whose activation appears to be independent of tumor phenotype. - Eva, A (1983)
We surveyed 22 human hematopoietic tumors and tumor cell lines for sequences capable of transforming NIH 3T3 cells by DNA transfection. A primary human acute myelogenous leukemia, a chronic myelogenous leukemia cell line, and cell lines derived from three independent acute lymphocytic leukemias demonstrated oncogenes capable of conferring the transformed phenotype to NIH 3T3 cells through serial cycles of transfection. One of three transforming genes associated with acute lymphocytic leukemia cells (classified as thymocyte developmental stage II) was identified as the activated cellular homologue of the Kirsten murine sarcoma virus onc gene, kis, a member of the ras family of onc genes. A transforming gene, which was demonstrated to be common to several human myeloid and lymphoid tumor cells, was shown to be a distantly related member of the ras gene family. Thus, the NIH 3T3 transfection assay commonly detects related oncogenes in human hematopoietic tumor cells. Moreover, the activation of these oncogenes appears to be independent of the specific stage of cell differentiation or tumor phenotype.